APPLICATION OF THE ARDUINO PLATFORM IN MEDICAL DEVICE MODELING - Mamadaliyeva Umida Polatovna; Abdurazzaqov Xurshidjon Turg‘unboy o‘g‘li; Abdurazzoqova Inobat Olimjon qizi talabasi (Galaxy International Interdisciplinary Research Journal, 2023)
In solving medical problems, as well as in carrying out scientific and practical activities of treatment and diagnostics at a high-quality level, training of personnel who can properly use information technologies has a special place. The development of measuring devices for medical devices achieved by creating a complex project based on the same metrological basis, increasing the scope and quality of the entire field, and implementing the created project on a large scale. When modeling and configuring medical devices, work from the Arduino platform.